2021
DOI: 10.3390/cancers13040830
|View full text |Cite
|
Sign up to set email alerts
|

COMMD1, from the Repair of DNA Double Strand Breaks, to a Novel Anti-Cancer Therapeutic Target

Abstract: Lung cancer has the highest incidence and mortality among all cancers, with non-small cell lung cancer (NSCLC) accounting for 85–90% of all lung cancers. Here we investigated the function of COMMD1 in the repair of DNA double strand breaks (DSBs) and as a prognostic and therapeutic target in NSCLC. COMMD1 function in DSB repair was investigated using reporter assays in COMMD1-siRNA-depleted cells. The role of COMMD1 in NSCLC was investigated using bioinformatic analysis, qRT-PCR and immunoblotting of control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…COMMD1 is the most extensively characterised COMMD protein and is a pleiotropic factor, regulating many biological processes, including copper and cholesterol homoeostasis, ionic transport, protein aggregation, protein trafficking, oncogenesis, and oxidative stress 14 . Futhermore, COMMD1 was recently shown to function in the repair of DSBs and be a potential therapeutic target for the treatment of non-small cell lung cancer 15 . COMMD4, the subject of this study, has been previously shown to control NFkB activity in mammals 16 , to interact with cullins and modulate the activity of cullin-RING E3 ubiquitin ligase complexes 17 and be a good prognostic marker and therapeutic target in non-small cell lung cancer 18 .…”
mentioning
confidence: 99%
“…COMMD1 is the most extensively characterised COMMD protein and is a pleiotropic factor, regulating many biological processes, including copper and cholesterol homoeostasis, ionic transport, protein aggregation, protein trafficking, oncogenesis, and oxidative stress 14 . Futhermore, COMMD1 was recently shown to function in the repair of DSBs and be a potential therapeutic target for the treatment of non-small cell lung cancer 15 . COMMD4, the subject of this study, has been previously shown to control NFkB activity in mammals 16 , to interact with cullins and modulate the activity of cullin-RING E3 ubiquitin ligase complexes 17 and be a good prognostic marker and therapeutic target in non-small cell lung cancer 18 .…”
mentioning
confidence: 99%
“…The research also revealed that the upregulation of COMMD1 increased the proliferation of NSCLC cells and was associated with a bad prognosis for patients. Even COMMD1 -knockdown might increase the radiation sensitivity of NSCLC cells ( 17 ). As a potential novel anticancer treatment target, the function of COMMD1 in NSCLC requires additional investigation.…”
Section: The Commd Protein Family and Tumorsmentioning
confidence: 99%
“…Although the majority of molecular mechanism research have focused on COMMD1, nearly all COMMD protein family members regulate tumor progression. For example, COMMD1 ( 17 ), COMMD4 ( 18 ), COMMD8 ( 19 ), and COMMD9 ( 20 ) regulate the proliferation, invasion, and metastasis of lung cancer. COMMD2 ( 21 ), COMMD3 ( 22 ), COMMD7 ( 23 ), COMMD8 ( 24 ), and COMMD10 ( 25 ) promote or inhibit hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation